Application of a phase change material to a thermoelectric ceiling radiant cooling panel as a heat storage layer. (November 2020) - Lim, Hansol; Kang, Yong-Kwon; Jeong, Jae-Weon
Abstract: The objective of this study was to propose and obtain a workable design of a phase change material integrated thermoelectric radiant cooling panel (PCM-TERCP) through numerical and experimental investigations of thermal performance. The proposed PCM-TERCP consists of thermoelectric modules (TEMs), heat sinks, insulation, and PCM layer between two aluminum panels. The PCM layer is a thermal energy storage which provides passive cooling without operation of TERCP by freezing the PCM during the operation period for shifting the electrical load to the off-peak period demand periods. A numerical model of the proposed cooling panel was developed to obtain a desirable configuration of the PCM layer such that it would maintain the surface temperature set-point of the panel during the operation period without the activation of the TEMs of the panel. The numerical model was validated by measurement and data acquired through a laboratory test of the PCM-TERCP mockup. The predicted results agreed well with the measurement data, within the 10% error bounds. A parametric study was carried out to determine the critical design parameters affecting the cooling performance of PCM-TERCP. The results indicated that the panel surface temperature was significantly affected by the number of heat fins inside the PCM and thickness of the PCM layer. A 10-mm-thick PCM layer with more than five heat fins per unit length of the panel was the most feasible solution among the several cases considered in this study for PCM-TERCP to satisfy the design requirements for application in a conditioned space. In addition, it was revealed that the liquid fraction of PCM should be under 0.6–0.65 for efficiently using the latent heat of PCM by enhancing the heat transfer of PCM. Highlights: A PCM integrated thermoelectric radiant cooling panel is proposed. A numerical simulation model of the proposed system was developed and validated. A feasible design for improve cooling capacity was investigated. The proposed system can provide passive cooling for at least 3 h.